A 10-GHz Inductorless Modified Regulated Cascode Transimpedance Amplifier for Optical Fiber Communication. (August 2021) - Semsar Parapari, Elmira; Daie Koozehkanani, Ziaddin; Toofan, Siroos
Abstract: This paper proposes a novel broadband inverter-based regulated cascode transimpedance amplifier for optical fiber communication. The proposed inductorless TIA is designed with a single-ended configuration, which is realized based on the modified regulated cascode structure. The conventional RGC is reformed by a new structure to provide higher loop gain, which leads to further lower the TIA input impedance. The presented TIA is designed and simulated using the 130-nm CMOS technology in the presence of 1 pF input photodiode capacitance. The post-layout simulation results show that the TIA provides a transimpedance gain of 47 dBΩ, a bandwidth of 10.1 GHz, and an input-referred current noise of 42 pA/ √ Hz. The circuit occupies an active area of 0.003 mm 2 and consumes 12.2 mW from a 1.3 V supply. Furthermore, the Monte Carlo and corner analysis are performed to verify the robustness of the proposed TIA.